2021
DOI: 10.1101/2021.11.16.468799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

piCRISPR: Physically Informed Deep Learning Models for CRISPR/Cas9 Off-Target Cleavage Prediction

Abstract: CRISPR/Cas programmable nuclease systems have become ubiquitous in the field of gene editing. With progressing development, applications in in vivo therapeutic gene editing are increasingly within reach, yet limited by possible adverse side effects from unwanted edits. Recent years have thus seen continuous development of off-target prediction algorithms trained on in vitro cleavage assay data gained from immortalised cell lines. Here, we implement novel deep learning algorithms and feature encodings for off-t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Deep learning models could effectively handle large volumes of complex data, capturing intricate patterns and achieving superior performance in predicting off-target activity. The development of deep learning-based prediction models also enabled utilization of physical features modelling the off-target activity problem with more depth [17]. Accurately quantifying uncertainty in off-target activity predictions is a crucial next milestone this study aims to address.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep learning models could effectively handle large volumes of complex data, capturing intricate patterns and achieving superior performance in predicting off-target activity. The development of deep learning-based prediction models also enabled utilization of physical features modelling the off-target activity problem with more depth [17]. Accurately quantifying uncertainty in off-target activity predictions is a crucial next milestone this study aims to address.…”
Section: Discussionmentioning
confidence: 99%
“…While conventional machine learning models have shown promising results, recent studies using deep learning techniques have demonstrated even better performance [16]. These models utilize novel sequence encoding strategies, feature engineering approaches by introducing physical features [17], class rebalancing techniques, and attention mechanisms [18] to improve prediction performance. While several models have been developed, most of them are primarily dedicated to the classification task, aiming to predict the activity status of the sgRNA-target interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating them, either by data combination or by a meta-predictor that considers the predictions of models trained on each data separately, may improve prediction performance. Second, the efficiency of assays for measuring the genome-wide activity of CRISPR/Cas9 nucleases in cellula is limited by chromatin accessibility and other epigenetic factors (31; 58; 44). Therefore, including such information in our models may provide more insights regarding their potential for future improvements.…”
Section: Discussionmentioning
confidence: 99%
“…We trained three deep-neural-network architectures (inspired by pi-CRISPR (44) and DeepHF (45) architectures) for off-target classification and regression tasks, leveraging multilayer-perceptron (MLP), gated-recurrent-unit (GRU), and embedding techniques. The first architecture, which we denote by MLP-Emb , begins with an embedding layer of size 44, which transforms each 25-long one-hot-encoded aligned nucleotide pair into a 44-long real vector representation.…”
Section: Methodsmentioning
confidence: 99%